Development of A Training Module for Preparing Testlet Questions to Improve Competency of Chemistry Teachers - Menik Purpuniyanti; Bambang Ismanto (Eduvest - Journal of Universal Studies, 2025)
The objective of this research is to evaluate the training provided to high school chemistry teachers in Boyolali Regency for developing learning evaluation instruments, specifically focusing on creating questions in Testlet format. This study employs a Research and Development (R&D) approach, utilizing a mixed-method strategy based on the ADDIE model. Data collection was conducted through interviews, documentation, and questionnaires, with validation achieved via triangulation of sources and methods. The development process followed seven stages: identifying potential and problems, data collection, product design, design validation, product revision, trial, and final revision, involving ten chemistry teachers from the region. Analysis was conducted using the methods of Miles and Huberman. Findings indicated a significant lack of participation among chemistry teachers in question preparation training, alongside inadequate resources and challenges such as limited time, low motivation, and insufficient understanding of the training content. To address these issues, a training module was developed to enhance teachers' competencies in preparing testlet questions. The module includes an introductory section, four learning activities, and a closing segment. Validation from module experts, material experts, and potential users yielded suitability scores of 80.88%, 88%, and 92%, respectively. After limited-scale testing, the training module demonstrated an N-gain score of 0.7646, translating to a 76.46% increase in competency. The results affirm the module's effectiveness in improving the skills of high school chemistry teachers in Boyolali Regency.